Enhancing trefoil germination under metal stress through Bradyrhizobium sp. (Lotus) inoculation - Degaichia, Hoceme Degaichia; Hamas, Farid; Boussahoua, Ahmed Ramzi; Bakria, Touati; Bouchenak, Fatima (Revista Mexicana de Ciencias Agrícolas, 2025)
This study investigates the effect of inoculation with Bradyrhizobium sp. (Lotus), a symbiotic rhizobacterium, on the germination of trefoil under stress induced by copper, cadmium, and their combination. The goal is to highlight the role of Bradyrhizobium sp. (Lotus) in mitigating copper and cadmium stress and enhancing the germination of trefoil, a spontaneous fodder species. The research, conducted in Blida (Algeria) in 2024, focuses on the physiological aspects of germination, including Total Germination Count (TCG), Time to mean germination (TMG), and inhibition of germination reversibility. Statistical analysis was performed using Manova at a 5% threshold. Results indicate that Bradyrhizobium sp. (Lotus) inoculation increases TCG values and reduces the germination lag phase from +168 h to 48 h. Additionally, germination inhibition is decreased by 20 to 30% compared to non-inoculated seeds, and physiological germination parameters improve under metal stress conditions. The findings suggest that Bradyrhizobium sp. (Lotus) may mitigate copper and cadmium stress by detoxification or chelation, thereby enhancing trefoil tolerance to these metallic trace elements during the germination stage.
Keywords: cadmium; copper; PGPR; physiology